Polycyclic aromatic hydrocarbon and its effects on human health: An overeview - Mallah, Manthar Ali; Changxing, Li; Mallah, Mukhtiar Ali; Noreen, Sobia; Liu, Yang; Saeed, Muhammad; Xi, He; Ahmed, Bilal; Feng, Feifei; Mirjat, Ali Asghar; Wang, Wei; Jabar, Abdul; et al. (Chemosphere (Oxford), 2022)
Polycyclic aromatic hydrocarbons (PAHs) are a class of chemicals of considerable environmental significance. PAHs are chemical contaminants of fused carbon and hydrogen aromatic rings, basically white, light-yellow, or solid compounds without color. Natural sources of pollution are marginal or less significant, such as volcanic eruptions, natural forest fires, and moorland fires that trigger lightning bursts. The significant determinants of PAH pollution are anthropogenic pollution sources, classified into four groups, i.e., industrial, mobile, domestic, and agricultural pollution sources. Humans can consume PAHs via different routes, such as inhalation, dermal touch, and ingestion. The Effect of PAHs on human health is primarily based on the duration and route of exposure, the volume or concentration of PAHs to which one is exposed, and the relative toxicity of PAHs. Many PAHs are widely referred to as carcinogens, mutagens, and teratogens and thus pose a significant danger to human health and the well-being of humans. Skin, lung, pancreas, esophagus, bladder, colon, and female breast are numerous organs prone to tumor development due to long-term PAH exposure. PAH exposure may increase the risk of lung cancer as well as cardiovascular disease (CVD), including atherosclerosis, thrombosis, hypertension, and myocardial infarction (MI). Preclinical studies have found a relationship between PAH exposure, oxidative stress, and atherosclerosis. In addition, investigations have discovered a relationship between PAH exposure at work and CVD illness and mortality development. This review aims to explain PAH briefly, its transportation, its effects on human health, and a relationship between environmental exposures to PAHs and CVD risk in humans. [Display omitted] •The primary routes of susceptibility to PAHs in the general population are breathing in outdoor and indoor air.•PAHs are moderately permanent and can be bio-accumulated.•PAH exposure may increase CVD risk, including atherosclerosis, hypertension, thrombosis, and myocardial infarction.•Studies have found a link between work-related exposure to PAHs and CVD and death.•The effect of PAHs on human health is primarily based on the duration and route of exposure and the relative toxicity of PAHs.